The Pursuit of Passion: Navigating Career Choices in Today’s Competitive Landscape - Babita Srivastava (International Journal of Children, 2025)
In today’s world, it’s common to see people chasing after name, fame, and wealth. While there’s nothing inherently wrong with ambition, this persistent pursuit often comes at the expense of genuine happiness, fun, and enjoyment. This is particularly evident among teenagers, who face immense pressure from their parents, peers, and societal expectations. Parents often place their unfulfilled dreams and aspirations onto their children, hoping they will achieve swift success and a lucrative income. This pressure sometime can drive students to excel in entrance exams like JEE, NEET, and UPSC, or secure prestigious government positions. In their quest for these goals, families might invest substantial amounts of money or leverage inherited assets, intensifying the stress on young minds. This pressure can be both emotional and financial, and many students bear it in silence. Even when they may prefer to explore other career paths, they might hesitate to voice their true desires. Consider that approximately 10 lakh students sit for the JEE exam each year, but only about 2 lakhs succeed. What becomes of the remaining 8 lakh? While some may enrol in some private institutions, others face severe stress or even despair, with troubling news emerging from cities like Kota. Instead of adhering to a singular path of success, why not encourage students to pursue their passions? Careers in fields such as photography, digital marketing, interior design, fashion design, or literature offer both respect and fulfilment. With so many diverse career options available today, we can support young people in finding paths that bring them both joy and success.
Keywords: Ambition; diverse career options; entrance exams; lucrative income; teenage pressure; unfulfilled dreams